Interlanguage pragmatics: A study into the acquisition of pragmatic competence in English as a foreign language context - Szczepaniak-Kozak, Anna (Peter Lang, 2014)
In this chapter the acquisition of pragmatic competence in English among advanced Polish learners of English is investigated. A sample of linguistic written data was collected in a discourse completion task of an open response format, planned as the first stage of a longitudinal study on acquisitional pragmatics. The responses provided are analyzed in terms of their structure, taking into account not only the directness of the speech act itself but also the external and internal mitigation used. On this basis, conclusions about the interlanguage pragmatic competence of the participants are drawn. Also, selected aspects of L2 pragmatics which may require further instruction are discussed.
Keywords: interlanguage pragmatics; requests; Polish learners of EFL